Chemical and Microbial Analysis of Bedding Material (Wood Shavings) Treated with Graded Levels of Aluminium Sulphate (Alum) - , A. A. Usman; , T. S. Olugbemi; , J. J. Omage; , K. M. Aljameel (Archives of Current Research International, 2021)
The study was carried out at the poultry unit of the Department of Animal Science teaching and research farm, Ahmadu Bello University, Zaria to determine the chemical and microbial analysis of poultry litter (wood shavings) treated with graded levels of alum. The alum used was obtained from the Sabon-gari market in Zaria, Kaduna State. The rates of alum application (prior to keeping the birds) was as follows: T1 control (normal wood shavings with no alum), T2 (5% alum by kg weight of wood shavings), T3 (10% alum by kg weight of wood shavings) and T4 (15% alum by kg weight of wood shavings). Five sets of litter samples were obtained fortnightly from each pen from different locations i.e. the four corners and center from which the microbial load, pH, total nitrogen (N), soluble reactive phosphorus, VFA and NH4+ concentration were measured. The result shows significantly (P<0.05) lower pH value in all the alum treated wood shavings groups (5%, 10% and 15% alum treated wood shavings) compared to the control. The result showed that significantly (P<0.05) lower total volatile fatty acid level was obtained in all the alum treated wood shavings groups (5%, 10% and 15% alum treated wood shavings) compared to the control untreated wood shaving group. The results showed a decrease in total bacteria, E. coli and Salmonella spp. load in alum treated wood shavings groups (5%, 10% and 15% alum treated wood shavings) compared to the control, while mould and yeast load was increased in all the alum treated wood shavings groups (5%, 10% and 15% alum treated wood shavings) compared to the control. The study conclude that treating wood shavings with alum can reduce microbial load of the litter, hence improve health and reduce mortality. Treating wood shavings with alum tends reduce the microbial load of the litter.